P3.085 Syphilis on the Rise in Germany - is It Temporary or a New Trend?. (13th July 2013) - Bremer, V; Marcus, U; Hamouda, O
Abstract : Background: Since 2001, laboratories in Germany are required to notify newly diagnosed cases of syphilis directly to the Robert Koch-Institut (RKI). The number of syphilis cases doubled 2001–04 to over 3000/year, remained stable until 2008 and decreased in 2009. Syphilis cases rose by 10% in 2010 and 22% in 2011. We analysed preliminary syphilis surveillance data from 2012 to assess whether this rise is continuing in 2012. Methods: Laboratories anonymously notify syphilis diagnoses to RKI and physicians complete laboratory findings with clinical information. Potential double notifications were identified by comparing available demographic data, diagnosis date, antibody titers, and clinical information. Syphilis was defined as: direct detection by microscopic or histological examination; positive screening test plus confirmation tests and VDRL/KBR activity, detection of IgM antibodies or clinical information consistent with syphilis. We described syphilis cases by month of diagnosis, age, sex and area of residence. If available, we analysed the data by transmission category. Results: Overall, 4380 cases were reported in 2012 (until 31.01.2013), corresponding to an 18.3% rise compared to 2011. The overall incidence was 5.3 per 100, 000 inhabitants, with highest incidences in Cologne (28.0), Munich (22.7) and Berlin (20.6). The median number of monthly notified cases increased from 253 in 2010 to 374 in 212. Notified cases increased in 12/16 federal states. Of notified cases, 93.1% were from men. The increase in 2012 was higher in women (26.7%) than men (17.8%). The likely mode of transmission was available for 72.8% of cases; of these, 75.7% were men who have sex with men (MSM) and in 16.4% heterosexual transmission was reported. Conclusion: Syphilis cases continue to increase since 2010, which is mainly attributable to MSM in large cities. Consistent condom use, early diagnosis and treatment are important to minimise the risk of syphilis and subsequently potential HIV transmission.